Study on the Properties and Synergistic Antioxidant Effects of Novel Bifunctional Fusion Proteins Expressed Using the UTuT6 System - Qi Yan; Jingyan Wei; Junxia Song; Mengna Li; Xin Guan; Jian Song (MDPI AG, 2023)
Important antioxidant enzymes, glutathione peroxidase (GPx) and superoxide dismutase (SOD), are involved in maintaining redox balance. They can protect each other and result in more efficiently removing excessive reactive oxygen species (ROS), protecting cells against injury, and maintaining the normal metabolism of ROS. In this study, human cytosolic GPx (hGPx1) and human phospholipid hydroperoxide GPx (hGPx4) genes were integrated into the same open reading frame with human extracellular SOD active site (SOD3-72P) genes, respectively, and several novel fusion proteins were obtained by using the UTuT6 expression system for the first time. Among them, Se-hGPx1UAG-L4-SOD3-72P is the bifunctional fusion protein with the highest GPx activity and the best anti-hydrogen peroxide inactivation ability thus far. The Se-hGPx4UAG-L3-SOD3-72P fusion protein exhibits the strongest alkali and high temperature resistance and a greater protective effect against lipoprotein peroxidation damage. Se-hGPx1UAG-L4-SOD3-72P and Se-hGPx4UAG-L3-SOD3-72P fusion proteins both have good synergistic and antioxidant abilities in H2O2-induced RBCs and liver damage models. We believe that this research will help with the development of novel bifunctional fusion proteins and the investigation of the synergistic and catalytic mechanisms of GPx and SOD, which are important in creating novel protein therapeutics.